Dynamical creation and detection of entangled many-body states in a chiral atom chain. (12th November 2019) - Buonaiuto, Giuseppe; Jones, Ryan; Olmos, Beatriz; Lesanovsky, Igor
Abstract: Open quantum systems with chiral interactions can be realized by coupling atoms to guided radiation modes in photonic waveguides or optical fibers. In their steady state these systems can feature intricate many-body phases such as entangled dark states, but their detection and characterization remains a challenge. Here we show how such collective phenomena can be uncovered through monitoring the record of photons emitted into the guided modes. This permits the identification of dark entangled states but furthermore offers novel capabilities for probing complex dynamical behavior, such as the coexistence of a dark entangled and a mixed phase. Our results are of direct relevance for current optical experiments, as they provide a framework for probing, characterizing and classifying classical and quantum dynamical features of chiral light–matter systems.